Probabilistic safety assessment in medical cyclotron facilities - C. Senthil Kumar; Suvadip Roy; Tapan Routh; M. Senthilkumar (Annals of Nuclear Energy, 2026)

Deciphering the consecutive electronic modulation and interfacial water activation of cobalt-incorporated tungsten diselenide electrocatalysts - Nasrin Banu G; Rama Prakash M; Ramesh Poonchi Sivasankaran; Muthupandi Senthilkumar; Wonyong Choi; Young Soo Kang; Bernaurdshaw Neppolian (Chemical Engineering Journal, 2026)

Predicting the metalloproteome of Deinococcus indicus DR1 through integrative structure and function annotation - Sweety Deena Ramesh; Giri Vasan; Shricharan Senthilkumar; Menaka Thambiraja; Deepa Sethi; Richa Priyadarshini; Ragothaman M. Yennamalli (Biodegradation, 2026)

Energy-Efficient Wireless Monitoring and Automated Aeration System for Sustainable Sugar Beet Pile Conditioning - M. Singla; Sunday J. Olakanmi; T. Senthilkumar; S. S. Panigrahi; C. B. Singh (Sugar Tech, 2026)

Isolation and complete genome analysis of Porcine Parvovirus 1 from swine with reproductive failure in southern India - P. Mohanapriya; S. Parthiban; K. Reshma; M. Parthiban; M. Murugan; A. Ramesh; K. Senthilkumar; P. Raja; P. Jalantha; Jagadish Hiremath; S. S. Patil; M. Kalyana Chakravarthi; et al. (Archives of Microbiology, 2026)

Aflatoxin detection and quality assessment in dried red chilli (Capsicum annum L.): A multifaceted approach using physical, microstructural, and machine learning techniques - M. Balasubramaniyan; J. Shavani Durga; V. Chelladurai; T. Senthilkumar; T. Krishnakumar; G. Jeevarathinam (Journal of Stored Products Research, 2026)

Exploring the Neuroprotective Role of the Sulfonamide Derivative KM11 in Ethidium Bromide-induced Demyelination in Zebrafish Model Through Modulation of Antioxidant and Inflammatory Cytokine Pathways - Karthikeyan Ramamurthy; Magesh Santhanakrishnan; S. Madesh; Prasannakumar Raja; Senthilkumar Palaniappan; Bader O. Almutairi; Mikhlid H. Almutairi; Muhammad Obaid M. Alotaibi; Yahya Madkhali; Manikandan Palanisamy; Kathiravan Muthu Kumaradoss; Jesu Arockiaraj (Molecular Neurobiology, 2026)

Pyrimidine Derivative, (E)-N-[4-(4-Chlorophenyl)-6-(4-Methylphenyl)Pyrimidin-2-yl]-1-(Furan-2-yl)Methanimine, Named BN5 Ameliorates Cognitive Dysfunction and Regulates esr1 and esr2b Expression in Female In Vivo Zebrafish Alzheimer Model - B. Aswinanand; Kumar Nallasivan Palani; Sanjai Dharshan Santhanam; Karthikeyan Ramamurthy; Senthilkumar Palaniappan; M. Valan Arasu; Ajay Guru; Muthumareeswaran Muthuramamoorthy; Kathiravan Muthu Kumaradoss; Jesu Arockiaraj (Journal of Neuroimmune Pharmacology, 2025)

SG06, a Chalcone Derivative Targets PI3K/AKT1 Pathway for Neuroprotection and Cognitive Enhancement in an Alzheimer’s Disease-Like Zebrafish Model - Santhanam Sanjai Dharshan; Meghana R; Shreya Madhankumar Rao; B. Aswinanand; Karthikeyan Ramamurthy; Muthumareeswaran Muthuramamoorthy; M. Valan Arasu; Kathiravan Muthu Kumaradoss; Ajay Guru; Senthilkumar Palaniappan; Jesu Arockiaraj (Molecular Neurobiology, 2025)

Sustainable development of cement-bonded particle boards using coir fiber edge trims and grain granulated blast furnace slag (GGBS): mechanical, thermal, and economic evaluations - Arya Ashok; Kiranbaalaji Senthilkumar; Karingamanna Jayanarayanan; K. M. Mini (Innovative Infrastructure Solutions, 2025)

Efficacy of 6-nitrobenzo[d]thiazol-2 Amine Derivative (N3) in Mitigating PTZ-Induced Epileptic Conditions Via Modulation of Inflammatory and Neuroprotective Pathways in-vivo Zebrafish - Karthikeyan Ramamurthy; S. P. Ramya Ranjan Nayak; S. Madesh; Siva Prasad Panda; K. Manikandan; Rajakrishnan Rajagopal; Ahmed Alfarhan; Senthilkumar Palaniappan; Ajay Guru; M. K. Kathiravan; Jesu Arockiaraj (Journal of Neuroimmune Pharmacology, 2025)

Recent progress in nanocellulose-based biocomposites for bone tissue engineering and wound healing applications - V. Parthasarathy; P. Senthil Kumar; Annie Aureen Albert; Senthilkumar Krishnasamy; M. Chandrasekar (Carbohydrate Polymers, 2025)

Pharmacognostical and Anatomical Insights into Sargassum polycystum: A Marine Brown Algae with Pharmaceutical and Medicinal Potential - R. Vijaya Gandhi; M. Senthilkumar; Dharmalingam Kirubakaran (Thalassas: An International Journal of Marine Sciences, 2025)

Genotype × Environment Interaction Analysis and Simultaneous Selection Using AMMI, BLUP, GGE Biplot and MTSI Under Drought Condition in Sweet Potato - K. H. Gowda; V. B. S. Chauhan; M. Nedunchezhiyan; C. Pradeepika; K. M. Senthilkumar; V. Chandra; G. Byju; M. R. Sahoo; K. Pati; R. Arutselvan (Journal of Soil Science and Plant Nutrition, 2025)

Anticancer potential of Calligonum comosum L.’Her. and Calligonum crinitum Boiss plants from United Arab Emirates - Wesam Khader; Mohamed K. Kayali; Tawfik M. Taj Eddin; Abdul Hadi S. S. S. Alameri; Mughair Abdul Aziz; Jaleel Kizhakkayil; Annadurai Senthilkumar; Ayesha S. Al Dhaheri; Abdul Jaleel (Advances in Traditional Medicine, 2025)

Short-Term Response of Mandous Severe Cyclone on Coastal Water Quality Along Southwestern Bay of Bengal, India - Subhasis Pradhan; P. Senthilkumar; Umakanta Pradhan; Subrat Naik; Rabindra Kumar Sahoo; Anitha Gera; Uma Sankar Panda; Pravakar Mishra; M. V. Ramana Murthy; P. Vipin Babu (Pure and Applied Geophysics, 2025)

Unveiling the diversity of gut microbes in green lacewings (Chrysopidae: Neuroptera) and their role as protagonist in nutrition - N. Karkuzhali; Y. S. Johnson Thangaraj Edward; N. Chitra; M. Senthilkumar; J. Ramalingam (Archives of Microbiology, 2025)

Genome analysis, identification, and expression analysis of nitrogen and potassium responsive genes in cassava - Swathy Sivan; Senthilkumar K. Muthusamy; M. N. Sheela; K. Arya; B. S. Revathi; P. V. Abhilash; R. S. Neethu; A. Pooja; B. S. Prakash Krishnan (Acta Physiologiae Plantarum, 2025)

Coastal spatial planning using object-based image analysis and image classification techniques - Senthilkumar C; Eatedal Alabdulkreem; Nuha Alruwais; Kavitha M (Journal of South American Earth Sciences, 2025)

Assessing the influence of hydrogeochemical characteristics and microbial communities on monsoon dynamics in groundwater quality in north Chennai city, India - S. Syed Ahamudul Rafeek; N. Mohamed Basith; M. Mohamed Hanipha; Meera Moydeen Abdul Hameed; S. Senthilkumar (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Recent advancements in nanotechnological approaches for pollution monitoring and environmental sustainability - J. Manjunathan; M. Revathi; H. Sowmya; S. S. Meenambiga; R. Sudha; B. Prakash; Senthilkumar Nangan; Lalitha Gnanasekaran; N. Thirumalaivasan (Clean Technologies and Environmental Policy, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Molecular Analysis of Classical Swine Fever Virus Associated Field Infections Evidence Novel CSFV Sub Genotype in Tamil Nadu, Southern India - S. Parthiban; B. Kowsalya; M. Parthiban; A. Ramesh; P. Raja; K. Gopal; S. Jaisree; R. Thangathurai; K. Senthilkumar (Indian Journal of Microbiology, 2024)

Tackling toxicity and stability using eco-friendly metal-halide ion substituted perovskite nanocrystals for advanced display color conversion - Maithili K. Rao; M. Selvakumar; M.G. Mahesha; Selvaraj Paramasivam; M.S. Santosh; S. Senthilkumar; Shiva Kant; Sami Rtimi (Chemical Engineering Journal, 2024)

Interactive behavior of cadmium ions onto polyethylene microplastics in aquatic system - D. M. Reddy Prasad; B. S. Naveen Prasad; R. Senthilkumar; K. Saravana Kumar; S. Manickkam (International Journal of Environmental Science and Technology, 2024)

Dissipation Kinetics and Residue Distribution of Imazethapyr in Urdbean (Vigna mungo (L.) Hepper) and Urdbean Field soil and its Effect on soil Microbial Population - Namrata Laskar; Krishnashis Das; Mrunalini Kancheti; M. Senthilkumar; Vaibhav Kumar; Kalpana Tewari; Chaitanya Prasad Nath (Bulletin of Environmental Contamination and Toxicology, 2024)

EV charging and fuel cell vehicle refuelling with distributed energy resources using hybrid approach - M. Senthilkumar; Sandeep Prabhu; U. Arun Kumar; R. Krishnakumar (Environment, Development and Sustainability, 2024)

Enhancing rainwater harvesting and groundwater recharge efficiency with multi-dimensional LSTM and clonal selection algorithm - N. Raghava Rao; Sree Pokkuluri Kiran; Tamboli Amena I; A. Senthilkumar; R. Sivakumar; M. Ashok Kumar; Sampathkumar Velusamy (Groundwater for Sustainable Development, 2024)

Polyethylene terephthalate waste derived nanomaterials (WDNMs) and its utilization in electrochemical devices - J. Manjunathan; K. Pavithra; Senthilkumar Nangan; S. Prakash; Kuldeep K. Saxena; Kuldeep Sharma; Khursheed Muzammil; Deepak Verma; Jenita Rani Gnanapragasam; R. Ramasubburayan; M. Revathi (Chemosphere, 2024)

Recent advances in microbial-assisted degradation and remediation of xenobiotic contaminants; challenges and future prospects - A.K. Priya; M. Muruganandam; Anuj Kumar; N. Senthilkumar; Mohd Shkir; Bidhan Pandit; Muhammad Imran; Chander Prakash; Mohd Ubaidullah (Journal of Water Process Engineering, 2024)

Validation, dissipation kinetics and monitoring of flonicamid and dinotefuran residues in paddy grain, straw, its processed produces and bran oil using LC-MS/MS - Ashok Kumar Karedla; R. Surya Raj; S.V. Krishnamoorthy; A. Suganthi; K. Bhuvaneswari; S. Karthikeyan; P. Geetha; M. Senthilkumar; S. Jeyarajan Nelson (Food Chemistry, 2024)

Single-Atom catalysts for oxygen reduction reaction and methanol oxidation reaction - Jasvinder Kaur; Vivek Sharma; Dipak Kumar Das; Bidhan Pandit; Mohd Shahzad Samdani; Mohd Shkir; M. Aslam Manthrammel; Senthilkumar Nangan; V. Jagadeesha Angadi; Mohd Ubaidullah (Fuel, 2024)

Engineering of hollow mesoporous Fe-graphitic carbon Nitride@CNTs for superior electrocatalytic oxygen reduction reaction - Anuj Kumar; Ram K. Gupta; Mohd Ubaidullah; Abdullah M. Al-Enizi; Bidhan Pandit; Senthilkumar Nangan; V. Jagadeesha Angadi; Ghulam Yasin (Fuel, 2024)

Waste plastics derived nickel-palladium alloy filled carbon nanotubes for hydrogen evolution reaction - Senthilkumar Nangan; Thirumalaivasan Natesan; Wiwittawin Sukmas; Manunya Okhawilai; Kaliyamoorthy Justice Babu; Prutthipong Tsuppayakorn-aek; Thiti Bovornratanaraks; Tawan Wongsalam; Vrince Vimal; Hiroshi Uyama; Abdullah M. Al-Enizi; Lavish Kansal; et al. (Chemosphere, 2023)

Exploring emotional contagion in zebrafish: A virtual-demonstrator study of positive and negative emotions - Daniel Burbano; Sahana Senthilkumar; M. Chiara Manzini (Behavioural Processes, 2023)

Ziziphus mauritiana-derived nitrogen-doped biogenic carbon dots: Eco-friendly catalysts for dye degradation and antibacterial applications - Subramani Rajapandi; Senthilkumar Nangan; Thirumalaivasan Natesan; Anuj Kumar; Govindaraj Dharman; M. Pandeeswaran; Deepak Verma; Mohd Ubaidullah; Bidhan Pandit; Navdeep Dhaliwal; Satbir S. Sehgal; Rajavel Rangappan; et al. (Chemosphere, 2023)

Genetic diversity analysis of Indian Cassava (Manihot esculenta Crantz) accessions using morphological and molecular markers - Swathy Sivan; Arya K; Sheela M N; Revathi B S; Prakash Krishnan B S; Senthilkumar K Muthusamy (South African Journal of Botany, 2023)

Halotolerant Nodule Rhizobial and Passenger Endophytes Alleviates Salinity Stress in Groundnut (Arachis hypogaea L.) - G. Oviya; Anandham Rangasamy; Manikandan Ariyan; R. Krishnamoorthy; M. Senthilkumar; N. O. Gopal; S. Thiyageshwari; S. Meena; S. Vincent (Journal of Plant Growth Regulation, 2023)

Azadirachta indica leaf extract mediated silver nanoparticles impregnated nano composite film (AgNP/MCC/starch/whey protein) for food packaging applications - Harish Pandian; Senthilkumar; Venkata Ratnam M; Naveenkumar M; Samraj S (Environmental Research, 2023)

Isolation and genetic analysis of Porcine circovirus 2 in southern India evidences high circulation of Porcine circovirus 2d genotype - S. Parthiban; A. Ramesh; Anbu Kumar Karuppannan; G. Dhinakar Raj; S. Hemalatha; M. Parthiban; K. Senthilkumar; D. Balasubramaniyam; R. Sumanth Kumar; S. Ranganatha; Chintu Ravishankar (Molecular Biology Reports, 2022)

Effective batch and column remediation of zinc(II) from synthetic and electroplating effluents using biochar from brown alga - R. Senthilkumar; Krishnan Saravanakumar; D. M. Reddy Prasad; B. S. Naveen Prasad; Feroz Shaik (International Journal of Environmental Science and Technology, 2022)

Molecular evidence of porcine circovirus 3 infection in swine: first report in southern India - S. Parthiban; A. Ramesh; G. Dhinakar Raj; Anbu Kumar Karuppannan; S. Hemalatha; M. Parthiban; Chintu Ravishankar; K. Senthilkumar; D. Balasubramaniyam (VirusDisease, 2022)

Molecular detection of porcine parvovirus 1–associated reproductive failure in southern India - S. Parthiban; R. K. V. Sowndhraya; P. Raja; M. Parthiban; A. Ramesh; G. Dhinakar Raj; K. Senthilkumar; D. Balasubramanyam; S. Hemalatha; R. Bharathi; Chintu Ravishankar; S. Thahira Parveen (Tropical Animal Health and Production, 2022)

Comparison of Single and Repeated Dosing of Anti-Inflammatory Human Umbilical Cord Mesenchymal Stromal Cells in a Mouse Model of Polymicrobial Sepsis - Barbara Fazekas; Senthilkumar Alagesan; Luke Watson; Olivia Ng; Callum M. Conroy; Cristina Català; Maria Velascode Andres; Neema Negi; Jared Q. Gerlach; Sean O. Hynes; Francisco Lozano; Stephen J. Elliman; et al. (Stem Cell Reviews and Reports, 2022)
Summary Mesenchymal stromal cells (MSCs) ameliorate pre-clinical sepsis and sepsis-associated acute kidney injury (SA-AKI) but clinical trials of single-dose MSCs have not indicated robust efficacy. This study investigated immunomodulatory effects of a novel MSC product (CD362-selected human umbilical cord-derived MSCs [hUC-MSCs]) in mouse endotoxemia and polymicrobial sepsis models. Initially, mice received intra-peritoneal (i.p.) lipopolysaccharide (LPS) followed by single i.p. doses of hUC-MSCs or vehicle. Next, mice underwent cecal ligation and puncture (CLP) followed by intravenous (i.v.) doses of hUC-MSCs at 4 h or 4 and 28 h. Analyses included serum/plasma assays of biochemical indices, inflammatory mediators and the AKI biomarker NGAL; multi-color flow cytometry of peritoneal macrophages (LPS) and intra-renal immune cell subpopulations (CLP) and histology/immunohistochemistry of kidney (CLP). At 72 h post-LPS injections, hUC-MSCs reduced serum inflammatory mediators and peritoneal macrophage M1/M2 ratio. Repeated, but not single, hUC-MSC doses administered at 48 h post-CLP resulted in lower serum concentrations of inflammatory mediators, lower plasma NGAL and reversal of sepsis-associated depletion of intra-renal T cell and myeloid cell subpopulations. Hierarchical clustering analysis of all 48-h serum/plasma analytes demonstrated partial co-clustering of repeated-dose hUC-MSC CLP animals with a Sham group but did not reveal a distinct signature of response to therapy. It was concluded that repeated doses of CD362-selected hUC-MSCs are required to modulate systemic and local immune/inflammatory events in polymicrobial sepsis and SA-AKI. Inter-individual variability and lack of effect of single dose MSC administration in the CLP model are consistent with observations to date from early-phase clinical trials. Graphical Abstract

A Review on Saponin Biosynthesis and its Transcriptomic Resources in Medicinal Plants - N. M. Kavya; Lateef Adil; Palanisamy Senthilkumar (Plant Molecular Biology Reporter, 2021)

Investigation of Geochemical Characterization and Groundwater Quality with Special Emphasis on Health Risk Assessment in Alluvial Aquifers, South Africa - P. P. Mthembu; V. Elumalai; M Senthilkumar; J. Wu (International Journal of Environmental Science and Technology, 2021)

Sustenance of Indian Moored Buoy Network During COVID-19 Pandemic – A Saga of Perseverance - R. Venkatesan; K. Jossia Joseph; C. Anoopa Prasad; M. Kalyani; M. Arul Muthiah; S. Ramasundaram; P. Murugesh; K. Thirumurugan; R. Sundar; B. Kesavakumar; G. Vengatesan; K. Ramesh; et al. (Frontiers in Marine Science, 2021)
The moored buoy network in the Indian Ocean revolutionized the observational programs with systematic time-series measurement of in situ data sets from remote marine locations. The real-time meteorological and oceanographic data sets significantly improved the weather forecast and warning services particularly during extreme events since its inception in 1997. The sustenance of the network requires persistent efforts to overcome the multitude of challenges such as vandalism, biofouling, rough weather, corrosion, ship time availability, and telemetry issues, among others. Besides these, the COVID-19 pandemic constrained the normal functioning of activities, mainly by delaying the maintenance of the network that resulted in losing a few expensive buoy system components and precious data sets. However, the improvements in the buoy system, in-house developed data acquisition system, and efforts in ensuring the quality of measurements together with “best practice methods” enabled 73% of the buoy network to be functional even when the cruises were reduced to 33% during the COVID-19 lockdown in 2020. The moored buoys equipped with an Indian buoy data acquisition system triggered high-frequency transmission during the Super cyclone Amphan in May 2020, which greatly helped the cyclone early warning services during the COVID-19 pandemic. The COVID-19 lockdown points toward the reliability and enhanced utility of moored buoy observations particularly when other modes of measurements are limited and necessitates more such platforms to better predict the weather systems. The present study analyzed the enhancement of the buoy program and improvisation of the buoy system that extended the life beyond the stipulated duration and enabled the high-frequency data transmission during cyclones amid the COVID-19 lockdown. The recommendations to better manage the remote platforms specifically in the event of a pandemic based on the operational experience of more than two decades were also presented.

Biostimulant activity of sulfated polysaccharide extract from red seaweed Halymenia dilatata on yield of Mung bean in greenhouse conditions - S. Vinoth; P. Gurusaravanan; M. Arun; M. Saradhadevi; N. Senthilkumar; P. Gowtham; S. R. Sivakumar (Journal of Applied Phycology, 2021)

Comparative bioefficacy of Bacillus and Pseudomonas chitinase against Helopeltis theivora in tea (Camellia sinensis (L.) O.Kuntze - M. Suganthi; S. Arvinth; P. Senthilkumar (Physiology and Molecular Biology of Plants, 2020)

Impact of landuse on the groundwater quality along coastal aquifer of Thiruvallur district, South India - S. Senthilkumar; B. Gowtham; M. Sundararajan; S. Chidambaram; J. Francis Lawrence; M. V. Prasanna (Sustainable Water Resources Management, 2018)

Fluoride hydrogeochemistry and its occurrence in drinking water in Morappur region of Dharmapuri District, South India - M. Panneer; R. Sivakumar; M. Senthilkumar (International Journal of Environmental Science and Technology, 2017)

Solute transport modelling for assessing the duration of river flow to improve the groundwater quality in an intensively irrigated deltaic region - E. Vetrimurugan; M. Senthilkumar; L. Elango (International Journal of Environmental Science and Technology, 2017)

Diagnosis of Mycobacterium bovis in Captive Sloth Bears (Melursus ursinus) by Polymerase Chain reaction - M. Veeraselvam; R. Sridhar; T. M. A. Senthilkumar; P. Perumal; M. G. Jayathangaraj (Proceedings of the Zoological Society, 2015)

Synthesis of novel 4-hydroxycoumarin derivatives: evaluation of antimicrobial, antioxidant activities and its molecular docking studies - M. Govindhan; K. Subramanian; K. Chennakesava Rao; K. Easwaramoorthi; P. Senthilkumar; P. T. Perumal (Medicinal Chemistry Research, 2015)

Effects of geological structures on groundwater flow and quality in hardrock regions of northern Tirunelveli district, southern India - M Senthilkumar; R Arumugam; D Gnanasundar; D S C Thambi; E Sampath Kumar (Journal of Earth System Science, 2015)

Are mini DNA-barcodes sufficiently informative to resolve species identities? An in silico analysis using Phyllanthus - R. SRIRAMA; B. R. GURUMURTHY; U. SENTHILKUMAR; G. RAVIKANTH; R. UMA SHAANKER; M. B. SHIVANNA (Journal of Genetics, 2014)

Homo-fermentative production of d-lactic acid by Lactobacillus sp. employing casein whey permeate as a raw feed-stock - Saurav Prasad; Katla Srikanth; Anil M. Limaye; Senthilkumar Sivaprakasam (Biotechnology Letters, 2014)

Geochemical processes controlling the groundwater quality in lower Palar river basin, southern India - M SENTHILKUMAR; L ELANGO (Journal of Earth System Science, 2013)

Methylobacillus rhizosphaerae sp. nov., a novel plant-associated methylotrophic bacterium isolated from rhizosphere of red pepper - M. Madhaiyan; S. Poonguzhali; M. Senthilkumar; D. Pragatheswari; K.-C. Lee; J.-S. Lee (Antonie van Leeuwenhoek, 2013)

In vitro cytotoxicity and induction of apoptosis by ruthenium(II) complexes in HL-60 and K-562 - S. Bhattacharya; Subhas S. Karki; R. Suresh; L. Manikandan; G. P. Senthilkumar; M. Gupta; Upal K. Mazumder; R. Balaji; K. Murali (Medicinal Chemistry Research, 2012)

Gamma-radiation induced modifications in substrate specificity of glucose dehydrogenase and carbon source utilization pattern of phosphate-solubilizing Pantoea strains - Young-Keun Lee; M. Senthilkumar; Il Yun Jeong; K. Annapurna; K. Swarnalakshmi (Biotechnology Letters, 2011)

Modelling the impact of a subsurface barrier on groundwater flow in the lower Palar River basin, southern India - M. Senthilkumar; L. Elango (Hydrogeology Journal, 2011)

Evaluation of the cocktail recombinant antigens, LipL32 and LipL41 for serodiagnosis of canine leptospirosis - M. Subathra; T. M. A. Senthilkumar; P. Ramadass; V. Ramaswamy (World Journal of Microbiology and Biotechnology, 2011)

Influence of hydraulic retention time in a two-phase upflow anaerobic sludge blanket reactor treating textile dyeing effluent using sago effluent as the co-substrate - M. SenthilKumar; G. Gnanapragasam; V. Arutchelvan; S. Nagarajan (Environmental Science and Pollution Research, 2011)

Recycle in upflow anaerobic sludge blanket reactor on treatment of real textile dye effluent - G. Gnanapragasam; M. Senthilkumar; V. Arutchelvan; P. Sivarajan; S. Nagarajan (World Journal of Microbiology and Biotechnology, 2010)

Serodiagnosis of bovine leptospirosis by IgG-Enzyme-Linked Immunosorbent Assay and Latex Agglutination Test - T. M. A. Senthilkumar; M. Subathra; P. Ramadass; V. Ramaswamy (Tropical Animal Health and Production, 2010)

Hybrid performance for yield and yield components in cardamom (Elettaria cardamom Maton) - D. Prasath; M. N. Venugopal; R. Senthilkumar; N. K. Leela (Euphytica, 2009)

Biocontrol Potential of Soybean Bacterial Endophytes Against Charcoal Rot Fungus, Rhizoctonia bataticola - M. Senthilkumar; K. Swarnalakshmi; V. Govindasamy; Young Keun Lee; K. Annapurna (Current Microbiology, 2009)

Detection and Characterization of ACC Deaminase in Plant Growth Promoting Rhizobacteria - V. Govindasamy; M. Senthilkumar; V. Mageshwaran; K. Annapurna (Journal of Plant Biochemistry and Biotechnology, 2009)

Purification and partial characterization of antifungal metabolite from Paenibacillus lentimorbus WJ5 - Young-Keun Lee; M. Senthilkumar; Jung-Hun Kim; K. Swarnalakshmi; K. Annapurna (World Journal of Microbiology and Biotechnology, 2008)

Collection of plant genetic resources from Andaman and Nicobar Islands - Z. Abraham; R. Senthilkumar; K. Joseph John; T. V. R. S. Sharma; N. V. Nair; M. Unnikrishnan; P. M. Kumaran; Johnson K. George; S. Uma; M. Latha; S. S. Malik; S. K. Mishra; et al. (Genetic Resources and Crop Evolution, 2008)

Induction of endophytic colonization in rice (Oryza sativa L.) tissue culture plants by Azorhizobium caulinodans - M. Senthilkumar; M. Madhaiyan; S. P. Sundaram; H. Sangeetha; S. Kannaiyan (Biotechnology Letters, 2008)

Purification and Partial Characterization of Antifungal Peptides from Soybean Endophyte-Paenibacillus sp strain HKA-15 - M. Senthilkumar; V. Govindasamy; P. Dureja; K. Annapurna (Journal of Plant Biochemistry and Biotechnology, 2007)

Role of Antibiosis in Suppression of Charcoal Rot Disease by Soybean Endophyte Paenibacillus sp. HKA-15 - M. Senthilkumar; V. Govindasamy; K. Annapurna (Current Microbiology, 2007)

Arbuscular mycorrhizal morphology and dark septate fungal associations in medicinal and aromatic plants of Western Ghats, Southern India - T. Muthukumar; M. Senthilkumar; M. Rajangam; K. Udaiyan (Mycorrhiza, 2006)

Effects of Copper Sulfate and Copper Nitrate in Aquatic Medium on the Restoration Potential and Accumulation of Copper in Stem Cuttings of the Terrestrial Medicinal Plant, Portulaca Oleracea Linn - S. Mohanapriya; P. Senthilkumar; S. Sivakumar; M. Dineshkumar; C. V. Subbhuraam (Environmental Monitoring and Assessment, 2006)

Plant Growth–Promoting Methylobacterium Induces Defense Responses in Groundnut (Arachis hypogaea L.) Compared with Rot Pathogens - M. Madhaiyan; B. V. Suresh Reddy; R. Anandham; M. Senthilkumar; S. Poonguzhali; S. P. Sundaram; Tongmin Sa (Current Microbiology, 2006)

Three-dimensional mathematical model to simulate groundwater flow in the lower Palar River basin, southern India - M. Senthilkumar; L. Elango (Hydrogeology Journal, 2004)

Molecular phylogeny of mangroves VIII: Analysis of mitochondrial DNA variation for species identification and relationships in Indian mangrove Rhizophoraceae - M. Lakshmi; M. Parani; P. Senthilkumar; Ajay Parida (Wetlands Ecology and Management, 2002)

Molecular phylogeny of mangroves VII. PCR-RFLP of trnS-psbC and rbcL gene regions in 24 mangrove and mangrove-associate species - M. Parani; M. Lakshmi; B. Ziegenhagen; M. Fladung; P. Senthilkumar; A. Parida (Theoretical and Applied Genetics, 2000)

Molecular phylogeny of mangroves V. Analysis of genome relationships in mangrove species using RAPD and RFLP markers - M. Parani; M. Lakshmi; P. Senthilkumar; Nivedita Ram; A. Parida (Theoretical and Applied Genetics, 1998)